Optimizing Ultrasonic Extraction of Enhalus acoroides to Enhance Physicochemical Traits and Antioxidant Activity - Mardiyanti, Siti; Anwar, Effionora; Desmiaty, Yesi; Sadiah, Siti (Tropical Biopharmaca Research Center, IPB University, 2025)
Enhalus acoroides is a seagrass species known for its antioxidant potential due to its flavonoid content, including quercetin. This study aimed to optimize the extraction time using the ultrasound-assisted extraction (UAE) method based on physicochemical parameters and antioxidant activity. The simplicia was extracted for 20, 30, and 40 minutes, each in triplicate, using 96% ethanol acidified with 1% HCl. The results demonstrated that extraction time significantly influenced the physicochemical properties, including yield (highest at 30 minutes: 40.2%), total phenolic content (1.153 mg GAE/g), total flavonoid content (0.318 mg QE/g), quercetin content (0.316 mg/g), and antioxidant activity (IC₅₀ = 58.44 ppm), whereas no significant effect was observed on total ash content. Qualitative phytochemical screening revealed the presence of alkaloids, flavonoids, tannins, saponins, and triterpenoids. Based on these findings, a 30-minute extraction time is recommended as the optimal condition for obtaining E. acoroides extract with the highest antioxidant activity.